COMPARATION OF ADSORPTION EFFECTIVENESS GAMMA-IRRADIATED SODIUM LAURYL SULPHATE (SLS) AND CETYLTRIMETHYL AMMONIUM BROMIDE (CTAB) AS AN INTEGRATION METHOD TO ENHANCE PERFORMANCE OF ACTIVATED CARBON - Ariyanti, Dhita
Activated carbon is a widely used material with various benefits such as energy storage, adsorbent, electronic components, drug delivery, fuel cells, and so on. Carbon activation is carried out through two methods, namely chemical and physical. The chemical method still has shortcomings, namely the presence of residues or chemical residues that are harmful to the surrounding environment, while the physical method requires high energy and power during the manufacturing process. This research accommodates novelity in integrating the use of the 60Co gamma radiation induction method as a clean, environmentally friendly and low energy method as a substitute for conventional chemical and physical methods. Carbon is activated through the addition of gamma-irradiated surfactant 60Co as a cross-linking and structure-degrading agent. SLS and CTAB surfactants were added to determine the comparison of their adsorption effectiveness on carbon, which was then applied as a Pb2+ cation adsorbent. AC/SLS was then irradiated with a dose range of 10 to 50 kGy, then characterized with several instruments. The results showed that 60Co gamma radiation had an effect on the effectiveness of adsorption of SLS and CTAB surfactants on carbon with optimum contact time and irradiation dose. The optimum contact time and irradiation dose for SLS adsorption on carbon is 20 minutes and 30 kGy with an adsorption capacity of 0.572 mg/g or 95.82%. This value has a difference of 16.369% compared to SLS adsorption without gamma irradiation. Meanwhile, CTAB adsorption on carbon has an optimum contact time and irradiation dose of 30 minutes and 30 kGy, where the adsorption capacity value is 0.381 mg/g or 63.586%. This value has a difference of 11.823% when compared with CTAB adsorption on carbon without gamma irradiation. The effect of gamma irradiation in AC/SLS on the C=C and C=O functional groups is significant with p values of 0.01631178 and 0.0239041; surface area (m2/gram) AC/SLS/? does not have a significant effect; pore volume (cc/gram) has a significant effect with a p value of 0.014758633; pore diameter (Å) does not have a significant effect, which means that pore stability is well maintained; and morphology changes occur, but are not significant. Meanwhile, gamma irradiation did not have a significant effect on the C=C and C=O AC/CTAB functional groups with a p value below 0.05; surface area (m2/gram) and pore volume (cc/gram) did not have a significant effect; Statistically, the pore diameter (Å) has a significant effect, but the phenomenon is that pore stability is well maintained; and morphology changes occur, but are not significant. From the comparison of the adsorption effectiveness of the two different surfactants on activated carbon above, one surfactant was then selected with conditions that were proven to be optimal for adsorption on activated carbon. Based on the results of comparing the effectiveness of surfactant adsorption of SLS and CTAB on carbon, it can be concluded that the absorption capacity of SLS is higher than that of CTAB, so the next stage is to determine several studies for the adsorption of SLS on carbon. The adsorption or adsorption model of SLS on modified activated carbon tends to follow the trend of the pseudo second order model. The largest regression value in the adsorption isotherm study was 0.991 which shows the Langmuir equation approach, with a k value of 0.5739 L/mg. This means that SLS adsorption on activated carbon follows the assumption that the SLS adsorption energy is uniform over the entire surface of the homogeneous activated carbon adsorbent and adsorption occurs in one layer or what is usually called a monolayer. Finally, the regression value in the thermodynamic study was obtained at 0.9947 with a slope of 2582 and an intercept of –4.6353. Calculation of thermodynamic data shows that SLS adsorption on activated carbon has a positive ?H value (21.466748 kJ/mol.K), which means the reaction runs endothermically and is chemisorption. Positive ?H also indicates the presence of van der Waals forces, dipole bonding forces, hydrogen bonds, and/or electron exchange coordination or the sharing of electrons in the formation of new bonds. The negative ?S value (–38.5378842 J/mol) means that the SLS adsorption process on the activated carbon surface has low irregularities between the active carbon–SLS liquid solid surface and no internal structure changes during the adsorption process. Gamma irradiation treatment with optimum doses of 30 and 40 kGy on AC/SLS was able to increase the Pb2+ cation adsorption capacity to 54.31% and 52.67% compared to AC/SLS without irradiation of 41.65%.